Analisis Kinerja Aparatur Desa Majakerta Dalam Meningkatkan Kepuasan Masyarakat - Mustofa, Zaenal; Maryono, Dicky (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the performance of Majakerta Village officials in managing social assistance and its impact on community satisfaction. The method used was a qualitative approach through in-depth interviews with village officials, social assistance recipients, and community leaders. The results indicate that despite efforts in the distribution procedure, shortcomings remain, such as a lack of transparency and communication with the community. Community satisfaction is influenced by information transparency and speed of distribution. It is recommended that village officials increase outreach and implement a more transparent system in managing social assistance.